IMPACT OF CLIMATE CHANGE ON RURAL GOAT FARMING IN EBONYI STATE, NIGERIA: IDENTIFYING EFFECTIVE ADAPTATION STRATEGIES - Anugwo, S.C.; Egwue, O.L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the Impact of Climate Change on Rural Goat Farming in Ebonyi State, Nigeria: Identifying Effective Adaptation Strategies. Based on the level of climate variability and large number of goat farmers, three local government areas namely, (Ohaozara, Ohaukwu and Ezza South LGAs) were randomly selected for this research. Multi-stage sampling technique was adopted for this research, with a total number of 84 respondents interviewed. Descriptive statistics and regression analysis were employed to analyze the objectives of the study. The results revealed that the mean age of the respondents was 27years implying that the farmers were still young and active. Goat farming was dominated by males (63.0%) and a smaller proportion of females (37.0%). Majority of the respondents were married (53.6%). The results showed that many of the farmers with mean of (12 years) were relatively educated and (39.3%) had 6 to 10 years of experience mitigating the effects of climate change on goat production in the study area. Regression result revealed the R2 value was 0.832, implying that the regression analysis explained 83.2% of the total variation in the model. Regression variables of age, household size, marital status, access to extension agents, ownership of goats and land ownership were all positive and statistically significant. Goat farmers should form cooperative associations so as to receive aid from the government in providing high resistant breeds of goats, portable water and drugs which will help in mitigating the effects of climate change on goat production in the study area.